Surveying Rubens' late landscapes new cartographic and archival sources on Het Steen - Watteeuw, Bert (2023)
Since the late nineteenth century, no new archival research on Peter Paul Rubens’ estate Het Steen has been published. Throughout the twentieth century, it has been assumed that art historians, such as Max Rooses, had depleted the archives for clues on Rubens’ country seat. No further targeted searches were undertaken. When the castle was acquired by the Flemish government in summer of 2019, the last private owner handed over a laundry basket filled with archival documents to a local circle of historians. While the trove contained but a handful of documents relating to the period in which Rubens inhabited Het Steen, it prompted a wider search for relevant archives. This included those left by various local and central administrative bodies and those formerly kept by neighbouring estates. Surprisingly, the search resulted in a wealth of new finds, including the 1635 deed of sale to Rubens, a surveyor’s map showing the first iconographic rendition of Het Steen after Rubens’ landscape at the National Gallery, and a second set of much larger surveyor’s maps which, through their relation with property ledgers, allow us to very precisely locate a substantial part of Rubens’ land holdings. Other documents testify to agricultural activity on the estate, such as timber trade or water management. Read in conjuction, these new archival and cartographic sources allow us to identify Rubens’ holdings in the Senne Valley and to glimpse some of the activities on the estate. Combined with a good knowledge of the terrain in this relatively small pocket of land, they also hold important keys to our reading of his two large landscapes, A view of Het Steen in the early morning (c. 1636) and The rainbow landscape (c. 1636), and several of his smaller late landscapes.
Keywords: Rubens, Peter Paul -- 1577-1640; Geschichte 1636; Landschaftsmalerei; Archivalien; Kasteel Het Steen -- Elewijt